Thinking about incarceration in South Africa: The Inside-out Outside-in interest group - Fourie, Eduard (PINS-Psychology in Society, 2015)
This article provides a reflective discussion as seen through the gaze of the recently formed Inside-out Outside-in South African Corrections Interest Group, about incarceration and the people who are affected by life inside and outside prisons. The main focus of the White Paper on Corrections in South Africa is the necessity to identify corrections as being focused on rehabilitation and as a responsibility that the Department of Correctional Services shares with society at large. Hawkins (1982) refers to correctional officers as “the other prisoners”, and in this reflective discussion, society at large is considered as “the other correctional officers” in reviewing attempts to give substance to the Department of Correctional Services’ objectives of corrections and rehabilitation in partnership with society. In particular, community engagement initiatives of the Inside-out Group linked to communities inside and outside the corrections environment in South Africa are highlighted.